Application of the “echo-synch protocol” to advance pregnancy onset in ewe lambs at the first reproductive season - Sotgiu, Francesca Daniela; Spezzigu, Antonio; Porcu, Cristian; Atzori, Alberto Stanislao; Sechi, Gian Simone; Pasciu, Valeria; Molle, Giovanni; Berlinguer, Fiammetta (Frontiers in Veterinary Science, 2023)
Introduction: This study assessed the efficacy and economic impact of a reproductive protocol based on repeated ultrasound scanning (US), associated with the use of GnRH, to advance pregnancy onset in ewe-lambs. Methods: Prepubertal ewe-lambs (n=133) were divided in three weight groups (High: HW n=35; Medium: MW n=65; Low: LW n=33). Thereafter, animals were randomly allocated into two subgroups: GnRH, ewe-lambs treated with GnRH analogue and then exposed to rams; CTR, ewe-lambs exposed to rams only. CTR groups were joined with rams as a single flock. GnRH groups were kept separated from rams receiving a single dose of gonadorelin (40 µg/head) and then were evaluated after a week with US. Animals showing corpora lutea received an injection of PGF2α analogue (100 μg/head) and then were joined with rams. The remaining ewe-lambs received a second dose of gonadorelin and were kept separate from rams. After another week, animals were checked again and the ones showing corpora lutea were injected with the PGF2α analogue, while the others received a third injection of gonadorelin. On the same day, all the animals were joined with rams. Pregnancies were confirmed within 30 days by US. The efficacy of the protocol was determined by assessing differences in the number of days required to achieve pregnancy rates of 25%, 50% and 75%, and in the total costs and incomes from birth to the end of first lactation within groups. Results: GnRH-MW group showed the best performances in reaching the threshold pregnancy rates of 25, 50 and 75% but the effect of treatment was significant only at 25% threshold (P<0.01). Both Low groups displayed an overall poorer performance at 50 and 75% thresholds than Medium and High weight groups (P=0.01 and P<0.01 respectively). The GnRH administration did not advance pregnancy onset in GnRH-HW compared with CTR-HW. In the balance between costs and income, the HW-CTR and MW-GnRH groups showed higher gross margin than the other groups. Conclusion: Using the US/GnRH protocol in ewe-lambs appears technically and economically effective in animals that have not reached the optimal weight at the first breeding season, advancing ewe-lambs’ pregnancies and increasing farm profitability.